Age differences in control beliefs regarding health: control, strategy and capacity - Bernardes, S.F.; Lima, M. L. (British Journal of Health Psychology, 2006)
Objectives. A new model of perceived control has been proposed (Skinner, 1995) in which 3 types of control-related beliefs were distinguished: control, strategy and capacity. This model has not yet been applied to health issues. Hence, the main purpose of this study was to apply it to the health domain, exploring age differences in the way children and teenagers conceptualize control-related beliefs. Design and setting. A prospective age cohort study was carried out with older children and teenagers attending public schools in Lisbon's metropolitan area. Method. A newly developed instrument (HPCQ) was administered to 188 healthy participants (91 6th graders and 97 11th graders). Results. Analyses of variance showed no age differences in individuals' strategy beliefs. Generally, children showed stronger capacity beliefs and a higher perceived control over their own health than teenagers. Hierarchical regression analyses showed that the belief in being a lucky person was a central predictor of control in later childhood. In adolescence, chance-related factors lost their predictive power, and effort and attributes-related beliefs remained controls' primary predictors. Conclusions. These results emphasize the heuristic value of this recent conceptualization of control-related beliefs. Moreover, they contribute to the development of more effective and reliable health-related school-based prevention/intervention programmes aiming at these particular age cohorts.